IPO Under-pricing Phenomenon Approach: Does Covid-19 Has a Negative Sectoral Impact? - Rini Dwiyani Hadiwidjaja Hadiwidjaja; Arianto Muditomo; Yanuar Trisnowati (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
An initial public offering (IPO) refers to the process of offering shares of a private corporation to the public in a new stock issuance. An IPO allows a company to raise capital from public investors. This study aims to prove the sectoral impact of the Covid-19 pandemic in Indonesia. Qualitative identification through content analysis on public online media and report documents on the results of analysis by research institutes and consultants identifies potential negative impacts on several industrial sectors as a result of the Covid-19 pandemic throughout 2020, but on the other hand, IPO action on the Indonesian capital market in 2020 still ongoing. Previous research has not been found specifically that analyzes the relationship between the impact of Covid-19 on industry and the performance of IPO actions per industrial sector, then through the IPO under-pricing phenomenon approach, empirical evidence is carried out. This research uses secondary data for the initial returns of 315 companies that conducted IPO actions during the period 2010 to 2020 on the Indonesian capital market and testing using a paired sample test on the population of IPO actions before and during the Covid-19 pandemic, the results of this study indicate that simultaneously in all the corporate sector did not find any statistically significant difference in initial returns between the period before and during the pandemic. This shows that the Covid-19 pandemic does not directly impact the behavior of capital market investors, especially in making investment decisions in the primary market.